2006
DOI: 10.1038/nm1425
|View full text |Cite
|
Sign up to set email alerts
|

Conditional ablation of Stat3 or Socs3 discloses a dual role for reactive astrocytes after spinal cord injury

Abstract: In the injured central nervous system (CNS), reactive astrocytes form a glial scar and are considered to be detrimental for axonal regeneration, but their function remains elusive. Here we show that reactive astrocytes have a crucial role in wound healing and functional recovery by using mice with a selective deletion of the protein signal transducer and activator of transcription 3 (Stat3) or the protein suppressor of cytokine signaling 3 (Socs3) under the control of the Nes promoter-enhancer (Nes-Stat3(-/-),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
536
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 845 publications
(562 citation statements)
references
References 30 publications
22
536
2
2
Order By: Relevance
“…At the subacute phase, astrocytes migrate to compact the lesion, presumably secluding the inflammatory cells to prevent them from spreading into the parenchyma of the spinal cord (Okada et al, 2006). In our study, when spinal cord injury and melatonin group were compared, ependymal cells showed regular distribution around the canalis centralis, mild hypertrophy in the cells and intense and regular distribution of nerve fibrils in the bipolar appearance of the funicular cells.…”
Section: Resultsmentioning
confidence: 51%
“…At the subacute phase, astrocytes migrate to compact the lesion, presumably secluding the inflammatory cells to prevent them from spreading into the parenchyma of the spinal cord (Okada et al, 2006). In our study, when spinal cord injury and melatonin group were compared, ependymal cells showed regular distribution around the canalis centralis, mild hypertrophy in the cells and intense and regular distribution of nerve fibrils in the bipolar appearance of the funicular cells.…”
Section: Resultsmentioning
confidence: 51%
“…This finding was consistent across different astrocytes obtained from different individuals used in our experiments. In the brain, STAT-3 possibly mediates a variety of biological processes, such as wound healing and cellular migration, and is a downstream effector of several cytokines involved in regulating astrogliosis [20][21][22]. A previous report utilizing Stat3 −/− mice showed that a large proportion of astrocytes failed to migrate toward and accumulate around a lesion center [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, STAT-3 possibly mediates a variety of biological processes, such as wound healing and cellular migration, and is a downstream effector of several cytokines involved in regulating astrogliosis [20][21][22]. A previous report utilizing Stat3 −/− mice showed that a large proportion of astrocytes failed to migrate toward and accumulate around a lesion center [20]. Moreover, Socs3 −/− mice displayed enhanced phosphorylation of STAT-3, rapid migration of reactive astrocytes, and severe glial scar formation, suggesting that STAT-3 is a key regulator of reactive astrocytes in the healing process after central nervous system injury.…”
Section: Discussionmentioning
confidence: 99%
“…Following brain lesion, astrocytes transform their cytoskeleton and migrate towards the lesion, where they are involved in oligodendrocyte repair and myelination, and reconstitution of the blood-brain barrier to prevent neuroinflammation (Bush et al, 1999;Faulkner et al, 2004). Moreover, when astrocytes are genetically inactivated, neuronal regeneration and neurite growth are impaired and demyelination occurs (Blain et al, 2006;Okada et al, 2006). In this respect, GPx4 expression in astrocytes after neurotrauma might be considered as a stress response aimed at neuroprotection to prevent further deterioration.…”
Section: An Emerging Role For Gpx4 In Neuropathological Conditions: Cmentioning
confidence: 99%